Women and đỏ̂i mới in Vietnam - Tran, Thi Van Anh (Woman Publishing House, 1997)
Part I. Women's Studies, Gender and Development ; Part II. The Position and Role of Women in Socio-Economic Renovation (DOI MOI) ; Part III. Women, Gender and Socio-Economic Policy Reform...